Labour-saving sowing tools for direct dry seeding of rice in Madagascar - Andriatsiorimanana, A.; Mujawamariya, Gaudiose; Tefy, Irina Andrianina; Harison Nomenjanahary, Fifaliana; Saito, Kazuki; Senthilkumar, Kalimuthu (2024)
Manual rainfed rice sowing is laborious and time-consuming, leading to delayed crop establishment due to labour shortage. To increase production and productivity, we proposed introducing single-row rotary seeders (for dibbling seeds) and fertiseeders (for simultaneous dibbling seeds and fertilizer) for smallholders. We evaluated ‘CFFAMMA seeder’ (already developed seeder by CFFAMMA), ‘New seeder’ (a newly designed seeder), and a fertiseeder in terms of sowing time, crop establishment, and yield in Madagascar. We also obtained farmers’ feedback on the machines’ effectiveness, desirability, their willingness to use, and to pay for it (farmer participatory approach). Finally, we evaluated the profitability of using these machines under rainfed conditions. On-farm experiments across four locations in the central highlands of Madagascar revealed up to 82% time savings using seeders and fertiseeder over two seasons compared with manual methods. The CFFAMMA seeder outperformed the other two, with similar numbers of missing hills, yield, and benefit–cost (B:C) ratios to manual sowing. Despite farmers’ desire to adopt seeders (96%), high cost of equipment acquisition remains a significant obstacle: farmers’ willingness to pay per unit of the equipment (US$8–11); actual price ($68–81). Addressing this financial burden is crucial for wider adoption. Though the seeders and fertiseeder achieved >80% time reduction for sowing and comparable yields to manual methods, fine-tuning of the tools for technical efficiency is also required for wider adoption.